Navigating the digital landscape: unraveling the interplay of challenge and hindrance components of technostress on employee voice behavior - Buzás, Barnabás; Simon, Adél Csenge; Kiss, Orhidea Edith; Faragó, Klára (Frontiers in Psychology, 2025)
IntroductionThe increasing digitalization of office work, especially with the rise of remote work, has amplified the impact of technostress in organizations. This study examines how technostress influences employee voice behavior. Grounded in the challenge-hindrance stressor framework, we hypothesize that certain aspects of technostress may positively affect voice behavior, psychological safety, intrinsic motivation, and affective commitment. Our findings provide insights for organizations to understand these dynamics and develop managerial strategies that foster positive workplace behaviors.MethodsWe conducted a cross-sectional study using an online questionnaire with office employees experienced in remote work (N = 361). Data were analyzed using three-step hierarchical regression models to assess the direct effects of technostress on voice behavior. Additionally, structural equation models (SEM) were used to explore indirect effects and the moderating roles of psychological safety, intrinsic motivation, and affective commitment.ResultsOur findings reveal that technostress consists of challenge and hindrance components. Techno-uncertainty and, to a lesser extent, techno-overload acted as challenge stressors, positively influencing voice behavior directly or through intrinsic motivation and affective commitment. Conversely, techno-insecurity and techno-complexity emerged as hindrance stressors. Techno-insecurity negatively affected all measured variables, while techno-complexity reduced voice behavior and psychological safety. We observed a positive linear relationship between challenge stressors and voice behavior, a negative linear relationship with hindrance stressors, and a weak U-shaped relationship between techno-insecurity and promotive voice.DiscussionOur study underscores the need to analyze technostress through the challenge-hindrance stressors framework, as its components can both enhance and hinder employee motivation and voice behavior. We interpret our findings through the lens of Conservation of Resources (COR) theory, emphasizing a proactive rather than a defensive or reactive approach. Additionally, we propose managerial strategies to encourage voice behavior in technostress-prone work environments.